Utilisation of Four Natural Absorbents in RemovingHeavy Metals from Sewage Water and Reducing their Accumulation in Maize Leaves - Al-Fahdawy Harith Sadaa Madhan; Salih Salih M.; Al-Fahdawy Mohammed Ismail Khalaf; Al-Hadethi Akram A. H.; Al-Fahdawi Omer Ismail; Abdulmajeed Amer Hashim; Al-Esawi Jabbar Sh. E. (Agriculture)
The general water quality has a direct influence on the ability to sustain life on the Earth. The aim of this study was to evaluate the efficiency of different natural adsorbents, namely phosphate rock, clay mineral (bentonite), peat moss, and soil in wastewater treatment. The laboratory experiment included columns experiment conducted as two factorial experiments. The first factor was water quality, which involved six types of water: river, untreated sewage water, sewage water treated with phosphate rock, sewage water treated with bentonite, sewage water treated with peat moss, and sewage water treated with soil. The second factor included two types of soil (two different soil textures), the first was clay loamy soil and the second was loamy soil. The treatments were randomly distributed following a randomized complete block design with three replications. The field study was represented by a pots experiment that included two types of soil textures, namely clay loamy and loamy soil. Heavy metals such as zinc, manganese, and iron were analysed in the water output from the columns to be used in the cultivation experiment as irrigation water. Overall the treatment combinations and the obtained results showed a significant reduction in the considered heavy metals. In this context, phosphate rock led to a decrease in zinc, manganese, and iron to 60.33, 54.00 and 55.30 mg/kg compared to untreated water which gave 63.33, 62.23 and 78.8 mg/kg. From an economic perspective, phosphate rock, was the most significant among the adsorbents under study, due to its availability and sustainability.